Comparative Evaluation of Heterologous Production Systems for Recombinant Pulmonary Surfactant Protein D - Salgado, Daniela; Fischer, Rainer; Schillberg, Stefan; Twyman, Richard M.; Rasche, Stefan (Frontiers in Immunology, 2014)
Commercial surfactant products derived from animal lungs are used for the treatment of respiratory diseases in premature neonates. These products contain lipids and the hydrophobic surfactant proteins B and C, which help to lower the surface tension in the lungs. Surfactant products are less effective when pulmonary diseases involve inflammatory complications because two hydrophilic surfactant proteins (A and D) are lost during the extraction process, yet surfactant protein D (SP-D) is a component of the innate immune system that helps to reduce lung inflammation. The performance of surfactant products could therefore be improved by supplementing them with an additional source of SP-D. Recombinant SP-D is produced in mammalian cells and bacteria (Escherichia coli), and also experimentally in the yeast Pichia pastoris. Mammalian cells produce full-size SP-D, but the yields are low and the cost of production is high. In contrast, bacteria produce a truncated form of SP-D, which is active in vitro and in vivo, and higher yields can be achieved at a lower cost. We compare the efficiency of production of recombinant SP-D in terms of the total yields achieved in each system and the amount of SP-D needed to meet the global demand for the treatment of pulmonary diseases, using respiratory distress syndrome as a case study.